Control of a 2 D.O.F direct drive robot arm using integral sliding mode control - KSM Kader Ibrahim, Babul Salam (2004)
High accuracy trajectory tracking is a very challenging topic in direct drive robot control. This is due to the nonlinearities and input couplings present in the dynamics of the robot arm. This thesis is concerned with the problems of modelling and control of a 2 degree of freedom direct drive arm. The research work is undertaken in the following five developmental stages; Firstly, the complete mathematical model of a 2 DOF direct drive robot arm including the dynamics of the brushless DC motors actuators in the state variable form is to be developed. In the second stage, the state variable model is to be decomposed into an uncertain model. Then, the Integral Sliding Mode Controller is applied to the robot arm. In the forth stage, perform the simulation. This is done through the simulation on the digital computer using MATLAB/SIMULINK as the platform. Lastly, the performance of Integral Sliding Mode Controller is to be compared with an Independent Joint Linear Control